Zdravstveno strukovno staleško pravo - Čizmić, Jozo; Cvitković, Miran; Klarić, Ante (University of Maribor Press, 2017)
Health Professional Law. This book is, by its purpose, a tutorial for postgraduate specialist medical studies at the Faculty of Law of the University of Split. In it’s content, following the explanation of the terms "medical law" and "health care professional law", the book presents the legal regulation of the status of health professionals (education, internships and professional exams, permanent professional training, conditions and approval for self - health professionals, healthcare professionals, professional medical certificates, specialization in the field of healthcare and specialist examination, recognition of foreign professional qualifications, permanent expert witness in health care). Also the book authors elaborate the rights, obligations and responsibilities of healthcare workers, dispute settlement (arbitration), supervision, medical secret, medical documentation), and in particular health insurance responsibility. In the second part of the book various forms of professional association of health professionals are presented, both compulsory association in professional chambers (with emphasis on public powers), and voluntary association in professional associations and trade union organizations of health workers.